Voice Features Across Essay Types Among Advanced EFL Learners - Esfandiari, Rajab; Sharifi, Hananeh (Pedagogika, 2023)
The present study reports on the findings of voice features across three text types under two different conditions. The results show significant differences in voice features in expository, but not in argumentative and descriptive text types, under timed and untimed conditions. The findings suggest that the analysis of voice features in different text types can inform writers of how successfully they create a balance in introducing their own perspectives.